Social Capital and the Performance of Water User Associations: Evidence from the Republic of Macedonia - Johannes Sauer; Matthew Gorton; Mile Peshevski; Dane Bosev; Darko Shekerinov (German Journal of Agricultural Economics (GJAE), 2010)
The paper assesses the performance of Water User Associations (WUAs) in the Republic of Macedonia. We assess performance in terms of membership rates, the satisfaction of members with their WUA and payment behaviour. Econometric analysis reveals that membership and satisfaction are positively related to farm size. Satisfaction and payment behaviour are strongly linked to structural and relational dimensions of social capital, particularly trust in senior managers of the WUA and the transparency with which resources are utilised. The conclusion highlights the importance of local factors in determining the success of WUAs. Key words: Water User Association; transition countries; social capital; microeconometrics
Keywords: 330; Mazedonien; Landwirtschaft; Wasserressourcen; Bewässerung; Gesellschaftliche Vereinigung